Association between coffee consumption and periodontal diseases: a systematic review and meta-analysis - Yeonjae Rhee; Yongjun Choi; Jeongmin Park; Hae Ryoun Park; Kihun Kim; Yun Hak Kim (BMC, 2022)
Abstract Background Several studies have demonstrated association between coffee consumption and periodontal diseases. However, no systematic review and meta-analysis was performed. Therefore, we performed a systematic review and meta-analysis to evaluate the association between coffee intake and periodontitis. Methods We defined PICO statement as "Do coffee drinkers have a higher association of periodontitis or tooth loss than non-coffee drinkers?". We searched for articles using the Embase and Medline databases. The odds ratio was used as an effect measure to evaluate the association between coffee and periodontitis We divided coffee intake doses into three groups: no intake (≤ 0.03 cups/day), low intake (0.03 < x < 1 cups/day), and high intake (≥ 1 cup/day). Cohort and cross-sectional studies were eligible for inclusion in this study. The Newcastle-Ottawa scale was used to qualitatively assess the risk of bias. The degree of heterogeneity between studies was quantified using I2 statistics. Results Six articles were analysed, including two cohort studies and four cross-sectional studies. The pooled unadjusted odds ratios of periodontitis were 1.14 (0.93-1.39), 1.05 (0.73-1.52), 1.03 (0.91-1.16) and 1.10 (0.84-1.45) in the 4 meta-analyses (coffee drinker vs. non-coffee drinker, high intake vs. low intake, low intake vs. no intake, high intake vs. no intake), respectively. Conclusion This is the first meta-analysis to investigate the relationship between coffee consumption and periodontitis. There was no relationship between coffee consumption and periodontitis. Further studies are required to assess whether a relationship between coffee consumption and periodontitis exists or not. PROSPERO registration number: CRD42022301341.